Características productivas y textiles de la fibra en alpacas Huacaya de Puno, Perú - Roque Gonzales, Lorenzo A. (2018)
The objective of this study was to determine the productive and textile characteristics of the fibre in Huacaya alpacas considering age (2, 4 and 6 years), sex and origin. Fibre samples were collected from the flanks of 120 alpacas from two communities of the Ayaviri district, Puno. The diameter, comfort factor and curvature index and fineness of yarn was determined using the computer analysis Optical Fiber Diameter 2000 and fibre length using the ASTM method. The diameter of the fibre and the fineness of yarn increased significantly with age (p<0.05), while the comfort index and wick length decreased significantly with the age of the animal (p<0.05). The curvature index was not affected by age, sex or origin of the animal. The sex and the community of origin did not affect the fibre diameter, the comfort index, the length of the wick or the fineness of the yarn. A negative and moderate correlation was found between the diameter of fibre with the index of curvature (r=-0.40) and comfort factor (r=-0.58), while a high correlation was observed between fibre diameter and fineness of yarn (r = 0.75).